PENGARUH BRAND EQUITY DALAM MEMBENTUK LIFESTYLE DAN CUSTOMER VALUE PADA PENGGUNA MEREK SMARTPHONE DI KOTA PEKANBARU (Jurnal Tepak Manajemen Bisnis, 2014)
This researchâs purpose is to discover and analyze the four dimensional brand equity effects whichconsist of brand awareness, perceived quality, brand loyalty, and brand association, either directly towardscustomer value or indirectly through lifestyle variable. This research is based on some of Pappuâs model (2005),by using brand awareness, perceived quality, brand loyalty, brand association, lifestyle, and customer valuedimensions. Measurement is done by the convenience sampling method. Data analysis is done by StructuralEquation Modeling using Partial Least Square.The research found that the prediction model is directly in agood state from the dimensions of brand equity with lifestyle, and only brand awareness has a positive effecttowards lifestyle. The other dimensions of perceived quality, brand loyalty, and brand association are notsignificantly and positively affected directly on lifestyle. However, on brand equity, there are only two dimensions- brand loyalty and brand association which positively affects customer value. Lifestyle dimension as interveningvariable in this research shows positive and significant effect in shaping customer value. As a whole, the modelon this research has a good predictive relevance value. In the next research, it is important to focus on creatinga non-monetary customer value. Perceived quality can be guided to increase brand loyalty and association, byincreasing brand function. Same goes with brand association, it can also be used to increase brand loyalty.Keywords : Customer Value, Brand Awareness, Perceived Quality, Brand Loyalty, Brand Association